IMPLEMENTASI LOAD BALANCING MIKROTIK JARINGAN INTERNET DI PARDAMEAN SIBISA, AJIBATA, TOBA SAMOSIR, SUMATRA UTARA - Berniman Gofindo Malau (Journal of Computer Science and Technology, 2022)
Today's communication needs are crucial with the advancement and development of increasingly advanced data communication technologies. To meet your data communication technology needs, you need to be wise when choosing an Internet Service Provider (ISP). You can use more than one Internet Service Provider (ISP) as a solution to meet your Internet requirements. Use load balancing, one of the routing technologies available to use multiple Internet Service Providers (ISPs) at the same time. There are many methods available for load balancing, one of which is the Per Connection Classifier (PCC) method. Per Connection Classifier (PCC) is a method that can be used for load balancing. PerConnectionClassifier (PCC) allows you to group connection traffic through a router into multiple groups. Therefore, the router remembers the gateway path passed at the beginning of the connection traffic, and subsequent packets still associated with the original connection are also forwarded with the same gateway path. The implementation results show that load balancing with the Per Connection Classifier (PCC) method achieves optimal results when using bandwidth from Indihome and Telkomsel Internet Service Providers (ISPs).